Comparison of Balanced Crystalloids versus Normal Saline in Critically Ill Patients: A Systematic Review with Meta-Analysis and Trial Sequential Analysis of Randomized Controlled Trials - Chen Y; Gao Y (Dove Medical Press, 2023)
Yi Chen,1- 3 Yongli Gao1- 3 1Emergency Department of West China Hospital, Sichuan University/West China School of Nursing, Sichuan University, Chengdu City, Sichuan Province, People's Republic of China; 2Institute of Disaster Medicine, Sichuan University, Chengdu City, Sichuan Province, People's Republic of China; 3Nursing Key Laboratory of Sichuan Province, Chengdu City, Sichuan Province, People's Republic of ChinaCorrespondence: Yongli Gao, Emergency Department of West China Hospital, Sichuan University/West China School of Nursing, Sichuan University, No. 37 Guoxue Alley, Wuhou District, Chengdu, Sichuan Province, 610041, People's Republic of China, Email gaoyongli0320@163.comBackground: Fluid resuscitation is routinely needed for critically ill patients. However, the optimal choice between crystalloids and normal saline is in heat debate.Objective: To conduct a meta-analysis comparing normal saline and balanced crystalloids in the treatment of critically ill patients with composite mortality as the primary outcome.Methods: PubMed, Embase, Medline, Web of Science, and Cochrane Library were searched from inception up to March 2022. Studies of critically ill adult patients assigned to receive normal saline or balanced crystalloids were included. We conducted a meta-analysis using an inverse variance, random-effects model in addition to trial sequential analysis (TSA). The primary outcome was composite mortality. Subgroup analyses were also conducted.Results: Eighteen full-text studies (n=36,224) were included. Balanced crystalloids were associated with lower mortality compared with normal saline (risk ratio [RR]=0.96; 95% confidential interval [CI] 0.93, 1; p=0.03; I2=0) and lower incidence of acute kidney injury/acute renal failure (RR =0.93; 95% CI = 0.87, 0.99; p=0.03). No significant difference was observed in other outcomes. In the sepsis patients, the balanced crystalloid showed a lower composite mortality rate compared with normal saline (RR =0.91; 95% CI = 0.85, 0.99; p=0.02). TSA analysis demonstrated that, with 80% power, the effect of balanced crystalloid is not larger than a 10% relative decrease in composite mortality compared with normal saline.Conclusion and Relevance: This study demonstrated that balanced crystalloids could be an optimal choice over normal saline in critically ill patients to a reduced composite mortality rate. In patients with sepsis, the difference is especially significant. Nonetheless, the optimal resuscitation fluid option between saline and balanced crystalloid solutions should be investigated further with more evidence.Keywords: balanced crystalloids, normal saline, critically ill, systematic review, meta-analysis